Converting Vehicle to LPG/Vigas: A Simple Calculator to Assess Project Feasibility - Eko Muh Widodo; Muhammad Imron Rosyidi; Tuessi Ari Purnomo; Muji Setiyo (Automotive Experiences, 2019)
One of the reasons for the slow conversion program from gasoline to LPG/Vigas is the uncertainty of profit or loss. Therefore, this article presents a simple calculator to assess the feasibility of investing in vehicle conversion, from gasoline to LPG/Vigas. Input parameters include estimated annual mileage, fuel consumption, gasoline prices, LPG / Vigas prices, the cost of the converter kit and its installation, engine standardization costs, maintenance costs with gasoline, and maintenance costs with LPG considered to produce output parameters that include Break Even Point (BEP), Payback period (PP), Net Present Value (NPV), and Internal Rate of Return (IRR).